Catalytic Co-pyrolysis of empty fruit bunch and high-density polyethylene mixtures over rice husk ash : Thermogravimetric, kinetic and thermodynamic analyses - Nadhilah Aqilah, Shahdan; Balasundram, Vekes; Norazana, Ibrahim; Ruzinah, Isha; Zainuddin, Abdul Manan (Elsevier Ltd, 2022)
Rice husk ash (RHA) has been used as a catalyst precursor but there are lack of studies on the application of the resulting catalyst. This study allows researchers to have an insight on using RHA-sourced catalysts in pyrolysis and be encouraged to utilize waste materials in the future. The goal of this study is to examine the effect of catalysts derived from rice husk ash (RHA) using the solvent-free method, labelled as RHA-T, on the catalytic co-pyrolysis of empty fruit bunch (EFB) and high-density polyethylene (HDPE) via thermogravimetric analyser (TGA). Comparisons were then made with co-pyrolysis and catalytic co-pyrolysis over raw RHA and Hydrogen-exchanged Zeolite Socony Mobil-5 (HZSM-5). Thermogravimetric analysis was conducted (EFB-to-HDPE mass ratio of 1:1, catalyst-to-feedstock mass ratio of 1:1) in a nitrogen atmosphere, where samples were heated from 30 °C until 700 °C (heating rate 20 °C/min). The order of runs with highest mass loss in the second phase is as follows, with the term ‘BP’ indicating the biomass-plastic feedstock: BP-RHA-T (98.17 wt%), BP-RHA (96.25 wt%), BP (86.82 wt%) and BP-HZSM-5 (70.59 wt%). Kinetic analysis using Coats-Redfern method and comparing between different diffusional reaction models showed that using BP-RHA-T follows a one-dimensional diffusion reaction, similar to the non-catalytic run. Using RHA-T resulted in higher activation energy (83.03 kJ/mol to 84.91 kJ/mol) compared to the non-catalytic run (62.39 kJ/mol to 68.97 kJ/mol). Thermodynamic analysis showed the pyrolysis runs were endothermic and non-spontaneous. Using RHA-T resulted in a higher change of enthalpy, a lower change of Gibbs free energy and a less negative change of entropy. It can be concluded that applying catalysts synthesized using low-cost materials like RHA can improve the degradation of EFB and HDPE via pyrolysis, compared to commercial HZSM-5 catalysts.